Evaluating the environmental friendliness, economics and energy efficiency of chemical processes : heat integration - Teresa Margarida Correia de Poço Mata (2003)
The design and improvement of chemical processes can be very challenging. The earlier energy conservation, process economics and environmental aspects are incorporated into the process development, the easier and less expensive it is to alter the process design. In this work different process design alternatives with increasing levels of energy integration are considered in combination with evaluations of the process economics and potential environmental impacts. The example studied is the hydrodealkylation (HDA) of toluene to produce benzene. This study examines the possible fugitive and open emissions from the HDA process, evaluates the potential environmental impacts and the process economics considering different process design alternatives. Results of this work show that there are tradeoffs in the evaluation of potential environmental impacts. As the level of energy integration increases process fugitive emissions increase while energy generation impacts decrease. Similar tradeoffs occur for economic evaluations, where the capital and operating costs associated with heat integration could be optimised. From the example designs considered here, an intermediate amount of energy integration produces the most economically beneficial and environmentally friendly process.